2021
DOI: 10.1038/s41598-020-79193-2
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of dengue outbreak in Selangor Malaysia using machine learning techniques

Abstract: Dengue fever is a mosquito-borne disease that affects nearly 3.9 billion people globally. Dengue remains endemic in Malaysia since its outbreak in the 1980’s, with its highest concentration of cases in the state of Selangor. Predictors of dengue fever outbreaks could provide timely information for health officials to implement preventative actions. In this study, five districts in Selangor, Malaysia, that demonstrated the highest incidence of dengue fever from 2013 to 2017 were evaluated for the best machine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 36 publications
2
40
0
1
Order By: Relevance
“…To the latter point, we find similarities with our work in that weather-based predictions performed well in some Brazilian municipalities, but not others. In another study that predicted a comparable binary outcome, weekly outbreak status, in Malaysian districts using weather information such as temperature and rainfall, the authors found an overall 70% accuracy using an SVM classifier [ 37 ], though noted that weather variables were not the most predictive in the model.…”
Section: Discussionmentioning
confidence: 99%
“…To the latter point, we find similarities with our work in that weather-based predictions performed well in some Brazilian municipalities, but not others. In another study that predicted a comparable binary outcome, weekly outbreak status, in Malaysian districts using weather information such as temperature and rainfall, the authors found an overall 70% accuracy using an SVM classifier [ 37 ], though noted that weather variables were not the most predictive in the model.…”
Section: Discussionmentioning
confidence: 99%
“…Specific machine learning algorithms such as SVM are used frequently for predictive analysis [53][54][55]. We divided input data into three classes in this work: confirmed COVID-19 cases, recovered cases, and deaths.…”
Section: Support Vector Machine (Svm) Model For Predictionmentioning
confidence: 99%
“…It contributes most to the national dengue hospitalisation in Malaysia. In the region, the dengue infection rates have increased significantly in the past decade as reported by Abd Majid et al (2021) and Salim et al (2021). Hii et al (2016) emphasise that dengue is a climate-sensitive infectious disease.…”
Section: Introductionmentioning
confidence: 99%
“…A variant of linear regression model is used to identify the entomological, epidemiological and environmental drivers that contributed to the dengue outbreak of two locations in Selangor state. Salim et al (2021) develop a supporting vector machine model that incorporates environmental variables including temperature, wind speed, humidity, and rainfall to predict dengue outbreaks.…”
Section: Introductionmentioning
confidence: 99%